2021
DOI: 10.1002/aet2.10632
|View full text |Cite
|
Sign up to set email alerts
|

Virtual multispecialty point‐of‐care ultrasound rotation for fourth‐year medical students during COVID‐19: Innovative teaching techniques improve ultrasound knowledge and image interpretation

Abstract: Objectives Point‐of‐Care Ultrasound (PoCUS) has been integrated into undergraduate medical education. The COVID‐19 pandemic forced medical schools to evolve clinical rotations to minimize interruption through implementation of novel remote learning courses. To address the students’ need for remote clinical education, we created a virtual PoCUS course for our fourth year class. We present details of the course’s development, implementation, quality improvement processes, achievements, and limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
2
14
0
2
Order By: Relevance
“…In a final example of novel approaches to meet the needs of students for remote clinical experiences during the Covid‐19 pandemic, a virtual POCUS course was created for fourth year medical students to replace an existing POCUS elective (Zavitz et al, 2021 ). Each class meeting used videoconferencing and began with a review of recorded lectures, reading assignments, and case studies, followed by a live demonstration of scanning technique by the instructor using an ultrasound instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a final example of novel approaches to meet the needs of students for remote clinical experiences during the Covid‐19 pandemic, a virtual POCUS course was created for fourth year medical students to replace an existing POCUS elective (Zavitz et al, 2021 ). Each class meeting used videoconferencing and began with a review of recorded lectures, reading assignments, and case studies, followed by a live demonstration of scanning technique by the instructor using an ultrasound instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional, face‐to‐face lectures were readily converted from in‐person to an online format, particularly at those institutions that had key electronic resources already blended into their curricula before the pandemic (Binks et al, 2021 ). However, online systems are not thought to be an effective substitute for an in‐person, hands‐on mode of instruction (Bowra et al, 2015 ; Alhasan & Al‐Horani, 2021 ; Zavitz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct interaction with synchronous assistance from the instructor was not provided. Zavitz et al created a virtual point-of-care ultrasound (POCUS) course [26]. Video conferencing software was used for online lectures and demonstration of scanning techniques with the transmission of an ultrasound signal and demonstration of corresponding transducer handling.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS is now being incorporated into medical student patient assessment curricula [2,3]. Several studies have demonstrated the feasibility of medical students using POCUS and have included teaching multiple POCUS applications to medical students simultaneously [2,4,5]. However, there are few studies demonstrating medical students' ability to accurately perform POCUS on pediatric patients and these studies have typically included one POCUS application taught at a time [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%